2020
DOI: 10.1162/netn_a_00120
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of the hippocampal memory system on the oculomotor system

Abstract: Visual exploration is related to activity in the hippocampus (HC) and/or extended medial temporal lobe system (MTL), is influenced by stored memories, and is altered in amnesic cases. An extensive set of polysynaptic connections exists both within and between the HC and oculomotor systems such that investigating how HC responses ultimately influence neural activity in the oculomotor system, and the timing by which such neural modulation could occur, is not trivial. We leveraged TheVirtualBrain, a software plat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…In line with this, Meister and Buffalo () discuss the possibility that the hippocampus has a role in directing eye movements in allocentric (spatio‐topic) coordinates, and specifically in inhibition of return. Recent studies showing that there are polysynaptic pathways linking hippocampal and oculomotor circuitry (Ryan et al, ; Shen, Bezgin, Selvam, McIntosh, & Ryan, ) provide a concrete neuroanatomical basis for hippocampal involvement in inhibition of return. Studies of people with medial temporal lobe damage that have revealed the importance of human hippocampal circuitry for some attention‐related phenomena (e.g., Chun & Phelps, ; Cosman & Vecera, ) provide one methodological model for how such an involvement might be explored.…”
Section: How Might Spontaneous Alternation and Inhibition Of Return Fmentioning
confidence: 99%
“…In line with this, Meister and Buffalo () discuss the possibility that the hippocampus has a role in directing eye movements in allocentric (spatio‐topic) coordinates, and specifically in inhibition of return. Recent studies showing that there are polysynaptic pathways linking hippocampal and oculomotor circuitry (Ryan et al, ; Shen, Bezgin, Selvam, McIntosh, & Ryan, ) provide a concrete neuroanatomical basis for hippocampal involvement in inhibition of return. Studies of people with medial temporal lobe damage that have revealed the importance of human hippocampal circuitry for some attention‐related phenomena (e.g., Chun & Phelps, ; Cosman & Vecera, ) provide one methodological model for how such an involvement might be explored.…”
Section: How Might Spontaneous Alternation and Inhibition Of Return Fmentioning
confidence: 99%
“…Reducing visual exploration therefore led to decreases in the relative strength of the functional connections across the network, and may have reduced information exchange between the oculomotor and medial temporal lobe networks ( Shen et al. 2016 ; Ryan, Shen, Kacollja, et al. 2020a ), resulting in declines in subsequent recognition memory.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, given the vast structural and functional network within which the oculomotor and HPC memory systems interact ( Shen et al. 2016 ; Ryan, Shen, Kacollja, et al. 2020 ), changes in patterns of visual exploration should also affect either the set of regions that comprise functionally connected networks, or the strength of those functional connections.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to fixed-viewing, free-viewing was associated with increased functional connectivity with the HPC, as well as with lateral and medial occipital cortex, and increased negative functional connectivity with regions such as the inferior parietal lobule, precuneus, anterior cingulate, lateral PFC, angular gyrus, and supramarginal gyrus. Reducing visual exploration therefore led to decreases in the relative strength of the functional connections across the network, and may have reduced information exchange between the oculomotor and medial temporal lobe networks 4,15 , resulting in declines in subsequent recognition memory. Thus, naturalistic viewing may coordinate responses (through correlated or potentially anti-correlated activity) across a broad network that includes regions responsible for the cognitive control of eye movements, perceptual processing of visual information, updating of spatial information, and memory 15,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…If the relationship between fixations and hippocampally-mediated memory is direct, then modifying rate and extent of visual exploration should modulate activity in the HPC as well as subsequent memory. Likewise, given the vast structural and functional network within which the oculomotor and hippocampal memory systems interact 4,15 , changes in patterns of visual exploration should also affect either the set of regions that comprise functionally connected networks, or the strength of those functional connections.…”
Section: Introductionmentioning
confidence: 99%